2023
DOI: 10.3390/f14030532
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from A Degradation of Planted Kandelia obovata Mangrove Forest in the Pearl River Estuary, China

Abstract: Kandelia obovata (L.) Druce and Sonneratia caseolaris (L.) Engl. are two dominant mangrove species in the subtropical coastlines of the Pearl River Estuary, China. The main aim of this study was to investigate the specific causes of K. obovata mortality versus S. caseolaris vitality on the west coast of Bao’an, Shenzhen, China and to propose sustainable management strategies for mangrove protection and future ecological planting restoration. Results showed that although both mangroves possessed simple and unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Indeed, a previous study reported that L. racemosa was widely considered a typical pioneer species found in the interior of mangroves and the transition to restinga forests [39]. This result was roughly identical to our latest study reporting that the importance values of the planted K. obovata and S. caseolaris were significantly higher than those of their accompanying species, such as S. apetala and B. gymnorrhiza, in the Pearl River Estuary, China [40]. Interestingly, the importance values of L. racemosa in terms of its tree and shrub layers first decreased and then increased with the increase in planting years; however, the dynamic result was the opposite in its seedling layer, which implied that with the increase in planting years, L. racemosa grew into shrubs and trees and dominated in their layers, while L. racemosa decreased gradually with the increase in planting years in the seedling layer since it was a light-loving species and not shade tolerant (Figure 2).…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, a previous study reported that L. racemosa was widely considered a typical pioneer species found in the interior of mangroves and the transition to restinga forests [39]. This result was roughly identical to our latest study reporting that the importance values of the planted K. obovata and S. caseolaris were significantly higher than those of their accompanying species, such as S. apetala and B. gymnorrhiza, in the Pearl River Estuary, China [40]. Interestingly, the importance values of L. racemosa in terms of its tree and shrub layers first decreased and then increased with the increase in planting years; however, the dynamic result was the opposite in its seedling layer, which implied that with the increase in planting years, L. racemosa grew into shrubs and trees and dominated in their layers, while L. racemosa decreased gradually with the increase in planting years in the seedling layer since it was a light-loving species and not shade tolerant (Figure 2).…”
Section: Discussionsupporting
confidence: 88%
“…As the implementers, local governments are required to abide by the negotiated restoration goal. However, for local governments, achieving the mangrove restoration goals on time is often a challenge [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%